Problem Pluralisme Agama di Indonesia - M. Adib Fuadi Nuriz; Achmad Reza Hutama Al Faruqi; Martin Putra Perdana (Universitas Darussalam Gontor, 2021)
Abstract This article examines the problem of religious pluralism that has always been echoed by liberals, so that the thinking of Muslims is often disturbed. This religious pluralism which often under the guise of tolerance easily poison the minds Muslims, especially ordinary people with their thoughts. In this article, the author examines the ideas of Prof. Harun Nasution, because he is one of the most famous figures in Indonesia with his work